2020
DOI: 10.1109/access.2020.3028474
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Drivers Predicting Behavioral Intention to Use m-Learning Management System: Partial Least Square Structural Equation Model

Abstract: This study aimed at reporting the drivers predicting Pre-Service English Teachers' (PSETs) behavioral intention to use m-learning Management Systems (m-LMS) in their learning activities. To achieve the purpose of the study, an extended technology acceptance model (TAM) was administered. Six drivers were included to examine 11 paths of the study framework. The instrument was adapted from previous studies and validated through content validity. Further, it was piloted to 76 PSETs for the reliability. Two hundred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 43 publications
4
18
0
2
Order By: Relevance
“…In accordance with the above, it is evident that there are more researchers who have used Subjective Norm, for example [59], [78], [82], [83], [1], [26], [85], [86], [87], [88], [89], [90], [91], [92], Experience in the internet & computer [59], [77], [81], [82], [84], [85], [93], [94], [95], [96], [97] Self-Efficacy [59], [83], [84], [85], [1], [71], [72], [73], [86], [95], [98], [99], [74], [97], Technical Support [59], [42], [73], [74], [83], [100], [101], [102] and Anxiety [72], [73],…”
Section: External Variables Of Tamsupporting
confidence: 59%
See 3 more Smart Citations
“…In accordance with the above, it is evident that there are more researchers who have used Subjective Norm, for example [59], [78], [82], [83], [1], [26], [85], [86], [87], [88], [89], [90], [91], [92], Experience in the internet & computer [59], [77], [81], [82], [84], [85], [93], [94], [95], [96], [97] Self-Efficacy [59], [83], [84], [85], [1], [71], [72], [73], [86], [95], [98], [99], [74], [97], Technical Support [59], [42], [73], [74], [83], [100], [101], [102] and Anxiety [72], [73],…”
Section: External Variables Of Tamsupporting
confidence: 59%
“…Researchers [78], [88] identified that Subjective Norms have no significant impact on Perceived Usefulness while other researchers [26], [59], [82], [86], [87], [89], [90], [91], have identified that Subjective Norms have a significant positive impact on Perceived Usefulness.…”
Section: Subjective Normsmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, KSC and employability were proposed to be predicted by educational process, practical activities, and research activities (Figure 1). The study implemented a cross-sectional survey design [25][26][27]. This design is described as quantitative research procedures, providing a survey administration to samples or the whole population.…”
Section: Design Of the Studymentioning
confidence: 99%